OPTIMALISASI RUANG PEMBUANGAN SAMPAH AKHIR TPA GUNUNG TUGEL - Chrisna Pudyawardhana (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2006)
TPA of Gunung Tugel which is located in countryside Kedungrandu, Subdistrict Patikraja. Taking possession of areal for the width of 5,4 ha. TPA’s managent of Gunung Tugel at its planning use the age plan 20 year. Thereby have a period of its exploiting. (1983 - 2003). TPA of Gunung Tugel, exploited with the method of open dumping, so that felt require to be made designed technical detail of according to condition actual which appear on the field to guarantee the function continueing as healthy TPA and do not generate the technical good problem, cultural social and also to society health. This study use 6 (six) of scenario alternative to be optimal of space TPA. From existing alternative, made by of most beneficial recommendation, by considering various aspect. Keyword: Optimalisasi, TPA of Gunung Tugel, Purwokerto.